Role of Surf Redfish (Actinopyga mauritiana) in Wound Incision Healing Activities of Diabetic Mice - Moriza Lesmana; Ermi Girsang; Ali Napiah Nasution; Adrian Adrian (Majalah Kedokteran Bandung, 2022)
It is estimated that 6% of the US population suffer from diabetes with 15% of them experience diabetic foot. Several studies have explored the various benefits of sea cucumber for human being, including its antioxidant nature. This study aimed to investigate the effect of surf redfish, one species of the sea cucumbers, in diabetic wound healing. This was an animal experimental study performed at the Pharmacology and Pharmaceutical laboratory of the Faculty of Pharmacy, Universitas Tjut Nyak Dhien Medan, Indonesia, during the period of February- July 2019. Twenty five mice in diabetic condition were divided into five groups: control, standard, ethanol extract of surf redfish-1, ethanol extract of surf redfish-2, and ethanol extract of surf redfish-3 3. The surf redfish was obtained from Lamreh Village in Aceh and the ethanol was extracted using the maceration method. The parameters used for evaluating the efficacy of surf redfish ethanol extract were blood glucose level, length of wound incision, and histopathological features. Surf redfish extract presented a significant reduction of blood glucose level which that followed the increase in the dose of the ethanol extract (p-value <0.05) where the most significant reduction was seen in the group with the highest dose on the last day. This trend was also seen for the length of the wound, where the reduction was significantly higher in treatment groups when compared to control (p-value <0.05). The histological study also confirmed the improvement in the clinical appearance of wound by showing significantly increased fibroblast cell number and collagen density (p-value <0.05). Overall, the surf redfish can help better incision's wound healing in diabetic condition.